The illustrated dictionary of toxicologic pathology and safety science - Sahota, Pritam S.; Spaet, Robert H.; Bentley, Philip; Wojcinski, Zbigniew (CRC Press, 2019)
The Illustrated Dictionary of Toxicologic Pathology and Safety Science provides descriptions of commonly used terms in toxicologic pathology with over 800 photomicrographs and illustrations to augment the written material. It also contains concise information, describing terms used in related areas such as anatomy, metabolism, drug development, and the allied fields of general toxicology. The definitions and descriptions were prepared and peer reviewed by editors and contributors who are known experts in toxicologic pathology, toxicology, and drug development.